The Impact of Social Media Marketing on Customer Behavior - Budhathoki, Netra Bahadur (Damak Campus Journal, 2024)
Social media is used by billions of people around the world and has quickly become one of the defining technologies of our time. Social media marketing has become one of the increasingly important aspects of customer behavior. Social media marketing is the practice of using social media platforms and tools to promote a business and connect with existing potential customers. The impact of social media marketing on customer behavior is a topic of paramount importance in today's digital age. This article aims to shed light on the ways in which social media marketing shapes customer behavior, providing valuable insights for businesses and marketers. The purpose of this article is to focus on where to believe the future of social media when considering customer behavior.